IMPACT OF BANK CREDIT ON MANUFACTURING SECTOR OUTPUT IN NIGERIA - Audu, Bello; Anfofum, Alexander Abraham; Bilkisu, Kabir Farouk (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
This study examines impact of bank credit on manufacturing sector output in Nigeria. The study sourced secondary data from CBN statistical bulletin for the period of 1986-2017. Manufacturing sector output serves as explained variable, while bank credit and inflation rate serve as explanatory variables. The study adopts ADF and PP tests of stationarity to determine the order of integration of the variables; ARDL model and ganger causality to test the hypotheses that bank credit does not have significant impact on manufacturing sector output; there is no significant long-run relationship between bank credit and manufacturing sector output; and there is no causality between bank credit and manufacturing sector output. Post-estimation tests were also conducted. The findings suggest that manufacturing sector output and bank credit at first difference, and inflation rate at level were stationary; unidirectional causality from manufacturing sector output to bank credit; bank credit exerts significant positive impact on manufacturing sector output; and significant long run relationship among variables. The model is, not serially correlated, homoscedastic, normally distributed, and stable. Based on the findings, the study recommends that existing functional policies such as credit rationing should be strengthened to attract potential investors in the manufacturing sector. Regulatory authorities should encourage the manufacturing sector through accessible and affordable bank credit that will encourage investors in the manufacturing sector to access adequate loan facility to enhance productivity in the sector; and specialized institutions should be licensed by CBN that will be solely responsible for allocating soft credit for manufacturing investment in Nigeria.